Вакансия третьего мужа: [роман] / Людмила Зарецкая - Зарецкая Людмила (Хозяйка своей судьбы, 2016)
Экземпляры: ф.12 (20160516) / Инвентарный номер: 47819 / Цена: 176.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-34 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6